Analysis of cracking of low-alloy copper stretched at elevated temperature (Fracture and Structural Integrity, 2015)
This paper presents both mechanical and structural aspects of micro-cracking of CuNi2Si copper alloy in CNCS grade revealed during the static tensile test in the temperature range between 20ºC and 800ºC. The purpose of this paper is to determine the impact of plastic deformation temperature and structural condition of the tested alloy on the type and mechanism of its cracking under specified deformation conditions. Therefore, the subject of the detailed metallographic analysis in a microscopic scale is the location of initiation and propagation of cracking, morphology of precipitations and their impact on the cracking process, nature and type of the fractures formed during material decohesion as well as microstructural analysis of the alloy by electron diffraction method. The obtained results allow the determination of the impact of analysed factors on cracking mechanism in the tested alloy as well as the specification of effective methods for limitation of the effects of cracking and thus the improvement in plasticity of alloy and workability of its products
Keywords: Low-alloy copper; Plastic deformation